Environmental Law with Sustainable Principles in Waste Bank Management in Sukoharjo Regency - Febriyanti, Nabila; Subekti, Rahayu; Ulfatun Najicha, Fatma (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
The author's aim in researching waste banks is to provide an understanding of waste management with a new paradigm in waste management, namely waste banks. Based on Law Number 18 of 2008, the use new paradigm of collect-transport-dispose in the Minister of Environment and Forestry Regulation Number 14 of 2021, namely with the issuance of a circular. This research was carried out using the legal research method. This type of empirical legal research is descriptive in nature, explaining what happened in Sukoharjo Regency and analyzed qualitatively. Results from several literature and interviews with the existence of waste bank regulations, local governments carry out and implement them. Sukoharjo Regency has the role of the environmental service in carrying out environmental management, especially waste management. However, there are areas where not all of them have active waste banks, so this research is interesting to examine waste banks in realizing the legal principles of a sustainable environment in Sukoharjo Regency. The research results show that the implementation of waste banks in Sukoharjo Regency must be further optimized to achieve environmental law objectives with the principle of sustainability and waste banks as a circular economy.